Isolasi dan Karakterisasi Morfologi Bakteri Halofilik dari Bledug Kuwu, Kabupaten Grobogan - Sabdaningsih, Anindita; Lunggani, Arina Tri (Departemen Biologi, Fakultas Sains dan Matematika, Universitas Diponegoro, 2020)
Bledug Kuwu is an area that has a fairly high salt content, this is caused by sea water trapped in the sedimentation process around the 18th century. Microorganisms that are able to live in extreme areas tend to have typical metabolic activities and can be utilized in industry. The purpose of this study was to characterize microbiologically, bacteria isolated from Bledug Kuwu, Kradenan District, Grobogan Regency, Central Java. The method used in this study was isolation on LB + NaCl media with NaCl levels of 10%, 12.5% and 15%. Characterization was done by Gram staining and motility test. The results obtained in samples from 3 sources, namely teak water, salt water and mud water, obtained 8 pure isolates. The seven isolates have the ability to grow optimally at 10% NaCl concentration so that these bacteria can be classified as moderate halophilic bacteria with the majority of species being coccus, Gram positive, and non motile.